If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -87 = 9 + x Solving -87 = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -87 + -1x = 9 + x + -1x Combine like terms: x + -1x = 0 -87 + -1x = 9 + 0 -87 + -1x = 9 Add '87' to each side of the equation. -87 + 87 + -1x = 9 + 87 Combine like terms: -87 + 87 = 0 0 + -1x = 9 + 87 -1x = 9 + 87 Combine like terms: 9 + 87 = 96 -1x = 96 Divide each side by '-1'. x = -96 Simplifying x = -96
| 6x^2+12x^2-7x= | | F(200)=100(1.04)200 | | X+7=1+7x | | -54=-42+n | | x+13y+8y= | | x+3-2x=75 | | 9*n=2.5 | | 2a+4a=1 | | Z+4(z+3)=15 | | 9=8y | | -46+12x=38+5x | | 20x-60=10x-10 | | 7x-a=6a | | 7+6x=-5x+95 | | 2(c+6)=5(5+12) | | 10x^2-30=5x^2+5 | | 6(x^2-10x+25)=1 | | 7-4x=-7x+10 | | 3x+24+7x-8=180 | | (x+12)+6+12+3(x+6)=58.5 | | 6x-36=3(x-5) | | 3x+24+7x-8=18 | | 65x+30=2505 | | 5X+3=5(2-3X) | | 5(x-5)-3= | | 8p+2q=36 | | k-23=-16 | | -2x+2=2x-6 | | 8k+8=0 | | F(X)=100(1.04)x | | x*x+9x+2y=18 | | x^2-49=95 |